Transformasi Kurikulum Pendidikan Islam di Indonesia - Lona, Efni Yuher; Arisman, Arisman; Syafiq, Muhammad; Demina, Demina (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to examine the transformation of the Islamic education curriculum in Indonesia in response to social, cultural, and global challenges. The method used is literature study by analyzing various documents, policies, and scientific studies related to the development of the national curriculum, especially in the context of Islamic education. The results of the research indicate that education plays a strategic role in shaping human resources that not only possess knowledge but also have strong competencies and moral values. The Indonesian education system has undergone six curriculum changes, starting from the 1968 Curriculum to the Education Unit Level Curriculum (KTSP), reflecting the changing needs of society. The 2013 Curriculum comes with a scientific approach that balances aspects of knowledge, skills, and attitudes while emphasizing the strengthening of character education. The Merdeka Curriculum, as the latest innovation, offers flexible, student-centered, and contextual learning according to local needs. This curriculum transformation demonstrates ongoing efforts to build an adaptive, humanistic, and transformative Islamic education system to produce superior generations with global competitiveness.